A kind of silicon dioxide aerogel thermal insulation felt and preparation method thereof
By mixing agarose and chitosan in the silica aerogel insulation felt, and adding silane coupling agent, the problem of difficult to take into account both the mechanical properties and the insulation properties of traditional silica aerogel insulation felt is achieved, and higher mechanical strength and insulation properties are achieved.
Patent Information
- Application Number
- CN202510012572.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-06
AI Technical Summary
Traditional silica aerogel insulation felts cannot have excellent mechanical properties and thermal insulation properties at the same time.
Compound fibers are prepared by mixing agarose and chitosan with each other, and the silane coupling agent triethoxysilylbutyraldehyde is added during the preparation process to enhance the compatibility and dispersion of the fibers, and finally obtain a silica aerogel insulation felt by supercritical carbon dioxide drying.
The mechanical strength and insulation performance of silica aerogel insulation felt are improved, and can be evenly distributed in the aerogel network, forming a complex internal structure to block heat conduction and enhance the thermal insulation effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a silica aerogel thermal insulation felt and a preparation method thereof. Background Art
[0002] Aerogel materials have great application prospects in the fields of sound insulation, thermal insulation, adsorption, construction, energy storage, etc. due to their low density, high specific surface area, low thermal conductivity, high porosity and low dielectric constant. However, their unique porous structure determines the poor mechanical properties of aerogels. In addition, traditional inorganic oxide aerogels have poor mechanical properties and are difficult to produce and apply in some fields. These problems limit the application of aerogel materials in daily life. Fiber insulation felt is a traditional inorganic thermal insulation material with good mechanical properties, but it has the defects of relatively high thermal conductivity and relatively large heat loss. Therefore, fiber felt and silica aerogel materials are combined with each other to form a new type of thermal insulation material.
[0003] Patent technology document CN109574622A discloses a method for preparing high temperature resistant silica aerogel insulation felt. The invention uses industrial sodium silicate as raw material, adopts fiber coupling, then washes with normal temperature water to remove impurities, and replaces with solvent ethanol in a continuous cycle, and finally dries at normal pressure to prepare silica aerogel insulation felt. The silica aerogel insulation felt has the advantages of high purity and high temperature resistance. The sodium ion content of the insulation felt is below 0.05wt%, and the thermal conductivity is less than 0.025W / (m·k) at 500℃.
[0004] Patent technical document CN108996985B discloses a method for preparing an aerogel felt thermal insulation material. The invention mixes orthosilicate, ethanol and water evenly, adds NH4F solution and ammonia water in sequence and stirs evenly to obtain silica sol A; stirs and mixes resin, initiator, coupling agent and hollow glass microbeads in a sealable container to obtain slurry B; first immerses the fiber felt in silica sol A, takes it out and then immerses it in the freshly prepared slurry B, repeats this operation 3-4 times to finally obtain an aerogel felt thermal insulation material that overcomes the problem of traditional silica aerogel felt shedding powder.
[0005] However, although the addition of inorganic ions can improve the mechanical properties of the material, the inorganic particles will inevitably occupy part of the pores, thereby affecting the thermal insulation performance of the material. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a silica aerogel thermal insulation felt and a preparation method thereof, so as to solve the problem that traditional silica aerogel thermal insulation felt cannot have excellent mechanical properties and thermal insulation properties at the same time.
[0007] Based on the above purpose, the present invention provides a method for preparing a silica aerogel thermal insulation felt, comprising the following steps:
[0008] S1: mixing the silicic acid solution, the agarose solution, and the composite fiber solution to obtain a premixed solution;
[0009] S2: Maintain the temperature of the premixed solution at 70-80°C, adjust the pH to 5-6, and maintain for 0.5-1h to obtain a gel solution;
[0010] S3: immersing the porous material in the gel solution for 12-24 hours to obtain a composite gel material;
[0011] S4: aging the composite gel material, replacing it with anhydrous ethanol, and finally drying it with supercritical carbon dioxide to obtain a silica aerogel thermal insulation felt;
[0012] The preparation steps of the composite fiber solution in step S1 are as follows: dissolving chitosan and agarose in a mixed solution of trifluoroacetic acid and dichloromethane, stirring evenly to obtain a mixed solution, then mixing triethoxysilyl butyraldehyde and perfluorooctylethyl trisiloxane with dimethyl sulfoxide, stirring evenly, adding them to the mixed solution, and mixing them in a planetary centrifuge for 20 minutes, stirring at room temperature for 24-36 hours, loading them into a glass syringe, electrospinning, crushing, sieving, and then drying them under a vacuum environment for 3-5 days to obtain composite fibers, dispersing them in deionized water to obtain a 1% composite fiber solution;
[0013] Preferably, in step S1, the weight ratio of the silicic acid solution, the agarose solution and the composite fiber solution is 2:1:0.2-0.3.
[0014] Preferably, the external electrostatic field of the electrospinning in step S1 is 15 kV / 12 cm, and the flow rate is 0.5 mL / h.
[0015] Preferably, the SiO2 content of the silicic acid solution in step S1 is 10%, and the preparation steps are as follows: dissolving sodium silicate powder in deionized water to obtain a sodium silicate solution with a SiO2 content of 10%, and then pouring the sodium silicate solution into a pretreated cation exchange resin to obtain a silicic acid solution with a SiO2 content of 10%.
[0016] Preferably, the pretreated cation exchange resin is 732 strong acid styrene cation exchange resin, which is first washed with hot water at 70-80°C until the effluent is colorless, then placed in an exchange column and soaked with 2 times the amount of 1 mol / LH2SO4 for 2 h, then rinsed with 4 times the amount of 2 mol / LH2SO4, and finally washed with a large amount of deionized water until neutral.
[0017] Preferably, the content of the agarose solution in step S1 is 5%.
[0018] Preferably, the agarose in step S1 is V-shaped.
[0019] Furthermore, the agarose solution is obtained by dissolving agarose in deionized water at 70° C. and stirring evenly;
[0020] Preferably, the relative molecular mass of the chitosan in step S1 is 200,000.
[0021] Preferably, the weight ratio of chitosan, agarose, trifluoroacetic acid, triethoxysilylbutyraldehyde, perfluorooctylethyltrisiloxane and dimethyl sulfoxide in step S1 is 5-6g:5-6g:45-55g:45-55g:0.2-0.3g:0.3-0.5g:50-100g.
[0022] Preferably, the pH adjustment in step S2 is performed using sodium hydroxide.
[0023] Preferably, the porous material in step S3 is selected from one of knitted glass fiber felt, melamine sponge, activated carbon fiber felt, glass fiber polyester mixed felt, viscous fiber felt and ceramic fiber felt.
[0024] Preferably, the aging temperature in step S4 is 50-80° C., and the aging time is 16-48 h.
[0025] Preferably, the supercritical carbon dioxide drying in step S4 is to place the aged gel material into a drying kettle, input CO2 into the drying kettle by a pump, maintain the supercritical temperature of the drying kettle at 45-65°C and the pressure at 10-18MPa; the flow rate of CO2 through the supercritical drying kettle is 50-2500L / h, and the drying time is 4-12h.
[0026] Furthermore, the present invention also provides a silica aerogel thermal insulation felt, which is prepared according to the above-mentioned preparation method of the silica aerogel thermal insulation felt.
[0027] Beneficial effects of the present invention: The silica aerogel thermal insulation felt of the present invention is prepared by mixing agarose and chitosan to prepare composite fibers, the composite fibers have better compatibility and dispersibility, can be evenly distributed in the aerogel network, and the composite fibers themselves have a relatively complex structure, which can improve the mechanical strength and thermal insulation performance of the thermal insulation felt;
[0028] The silica aerogel thermal insulation felt of the present invention further improves the compatibility and interaction between chitosan and agarose by adding a silane coupling agent triethoxysilylbutyraldehyde when preparing the composite fiber, thereby making the particle size of the fiber obtained by electrostatic spinning finer, and can further improve the flexural strength and thermal insulation performance of the thermal insulation felt;
[0029] The silica aerogel thermal insulation felt of the present invention is prepared by mixing agarose and chitosan to prepare composite fibers, and further adjusting the ratio between agarose and chitosan so that its thermal insulation performance can be further improved. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0031] The parameters of the supercritical carbon dioxide drying of the present invention are to input CO2 into the drying kettle by a pump, maintain the supercritical temperature of the drying kettle at 50°C and the pressure at 14MPa; the flow rate of CO2 through the supercritical drying kettle is 1500L / h, and the drying time is 10h.
[0032] Example 1: A method for preparing a silica aerogel thermal insulation felt, the specific steps are as follows:
[0033] (1) 5 g of chitosan and 5 g of agarose were dissolved in a mixed solution of 45 g of trifluoroacetic acid and 45 g of dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.2 g of triethoxysilyl butyraldehyde and 0.3 g of perfluorooctylethyl trisiloxane were mixed with 50 g of dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The mixture was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 24 h, the mixture was loaded into a glass syringe and electrospun under an applied electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The mixture was crushed and then dried under vacuum for 3 days. The mixture was dispersed in deionized water to obtain a 1% composite fiber solution.
[0034] (2) Wash 732 strong acid styrene cation exchange resin with hot water at 70°C until the effluent is colorless, then place the cation exchange resin in an exchange column and soak it with 2 times the amount of 1 mol / L H2SO4 for 2 h, then rinse it with 4 times the amount of 2 mol / L H2SO4, and finally wash it with a large amount of deionized water until it is neutral to obtain a pretreated cation resin; dissolve sodium silicate powder in deionized water to obtain 100 ml of a sodium silicate solution with a SiO2 content of 10%; dissolve agarose in deionized water at 70°C to obtain 100 ml of agarose solution with a content of 5%;
[0035] (3) Pour 200 ml of sodium silicate solution into 600 ml of pretreated cation exchange resin to remove sodium ions in the sodium silicate solution, thereby obtaining a silicic acid solution. Subsequently, 200 ml of 10% silicic acid solution was mixed with 100 ml of 5% agarose solution. Subsequently, 20 ml of composite fiber solution was added. After stirring evenly, sodium hydroxide was added to adjust the pH to 5 and maintained for 0.5 h. Then, the glass fiber felt was immersed for 12 h to obtain a composite gel material. The solution temperature needed to be maintained at 70 °C during the whole process.
[0036] (4) After the impregnation is completed, the composite gel material is aged at 50°C for 16 hours, fully replaced with anhydrous ethanol, and then dried with supercritical carbon dioxide to obtain silica aerogel insulation felt.
[0037] Example 2: A method for preparing a silica aerogel thermal insulation felt, the specific steps are as follows:
[0038] (1) 5.5 g of chitosan and 5.5 g of agarose were dissolved in a mixed solution of 50 g of trifluoroacetic acid and 50 g of dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.25 g of triethoxysilyl butyraldehyde and 0.4 g of perfluorooctylethyl trisiloxane were mixed with 80 g of dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The mixture was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 30 h, the mixture was loaded into a glass syringe and electrospun under an applied electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The mixture was broken and then dried under vacuum for 4 days. The mixture was dispersed in deionized water to obtain a 1% composite fiber solution.
[0039] (2) Wash 732 strong acid styrene cation exchange resin with hot water at 75°C until the effluent is colorless, then place the cation exchange resin in an exchange column and soak it with 2 times the amount of 1 mol / L H2SO4 for 2 h, then rinse it with 4 times the amount of 2 mol / L H2SO4, and finally wash it with a large amount of deionized water until it is neutral to obtain a pretreated cation resin; dissolve sodium silicate powder in deionized water to obtain 100 ml of a sodium silicate solution with a SiO2 content of 10%; dissolve agarose in deionized water at 70°C to obtain 100 ml of agarose solution with a content of 5%;
[0040] (3) Pour 200 ml of sodium silicate solution into 700 ml of pretreated cation exchange resin to remove sodium ions in the sodium silicate solution, thereby obtaining a silicic acid solution. Subsequently, 200 ml of 10% silicic acid solution was mixed with 100 ml of 5% agarose solution. Subsequently, 25 ml of composite fiber solution was added. After stirring evenly, sodium hydroxide was added to adjust the pH to 5.4 and maintained for 1 hour. Then, the glass fiber felt was immersed for 16 hours to obtain a composite gel material. The solution temperature needed to be maintained at 75°C during the whole process.
[0041] (4) After the impregnation is completed, the composite gel material is aged at 65°C for 30 hours, fully replaced with anhydrous ethanol, and then dried with supercritical carbon dioxide to obtain silica aerogel insulation felt.
[0042] Example 3: Preparation method of silica aerogel thermal insulation felt, the specific steps are as follows:
[0043] (1) 6 g of chitosan and 6 g of agarose were dissolved in a mixed solution of 55 g of trifluoroacetic acid and 55 g of dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.3 g of triethoxysilyl butyraldehyde and 0.5 g of perfluorooctylethyl trisiloxane were mixed with 100 g of dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The mixture was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 36 h, the mixture was loaded into a glass syringe and electrospun under an external electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The mixture was crushed and then dried under vacuum for 5 days. The mixture was dispersed in deionized water to obtain a 1% composite fiber solution.
[0044] (2) Wash 732 strong acid styrene cation exchange resin with hot water at 80°C until the effluent is colorless, then place the cation exchange resin in an exchange column and soak it with 2 times the amount of 1 mol / L H2SO4 for 2 h, then rinse it with 4 times the amount of 2 mol / L H2SO4, and finally wash it with a large amount of deionized water until it is neutral to obtain a pretreated cation resin; dissolve sodium silicate powder in deionized water to obtain 100 ml of a sodium silicate solution with a SiO2 content of 10%; dissolve agarose in deionized water at 70°C to obtain 100 ml of agarose solution with a content of 5%;
[0045] (3) Pour 200 ml of sodium silicate solution into 800 ml of pretreated cation exchange resin to remove sodium ions in the sodium silicate solution, thereby obtaining a silicic acid solution. Subsequently, 200 ml of 10% silicic acid solution was mixed with 100 ml of 5% agarose solution. Subsequently, 30 ml of composite fiber solution was added. After stirring evenly, sodium hydroxide was added to adjust the pH to 6 and maintained for 1 hour. Then, the glass fiber felt was immersed for 24 hours to obtain a composite gel material. The solution temperature needed to be maintained at 80°C during the whole process.
[0046] (4) After the impregnation is completed, the composite gel material is aged at 80°C for 48 hours, fully replaced with anhydrous ethanol, and then dried with supercritical carbon dioxide to obtain silica aerogel thermal insulation felt.
[0047] Comparative Example 1: A method for preparing a silica aerogel thermal insulation felt, the specific steps are as follows:
[0048] (1) 5.5 g of chitosan and 5.5 g of agarose were dissolved in a mixed solution of 50 g of trifluoroacetic acid and 50 g of dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.4 g of perfluorooctylethyl trisiloxane was mixed with 80 g of dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The mixture was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 30 h, the mixture was loaded into a glass syringe and electrospun under an applied electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The mixture was broken and then dried under vacuum for 4 days. The mixture was dispersed in deionized water to obtain a 1% composite fiber solution.
[0049] (2) Wash 732 strong acid styrene cation exchange resin with hot water at 75°C until the effluent is colorless, then place the cation exchange resin in an exchange column and soak it with 2 times the amount of 1 mol / L H2SO4 for 2 h, then rinse it with 4 times the amount of 2 mol / L H2SO4, and finally wash it with a large amount of deionized water until it is neutral to obtain a pretreated cation resin; dissolve sodium silicate powder in deionized water to obtain 100 ml of a sodium silicate solution with a SiO2 content of 10%; dissolve agarose in deionized water at 70°C to obtain 100 ml of agarose solution with a content of 5%;
[0050] (3) Pour 200 ml of sodium silicate solution into 700 ml of pretreated cation exchange resin to remove sodium ions in the sodium silicate solution, thereby obtaining a silicic acid solution. Subsequently, 200 ml of 10% silicic acid solution was mixed with 100 ml of 5% agarose solution. Subsequently, 25 ml of composite fiber solution was added. After stirring evenly, sodium hydroxide was added to adjust the pH to 5.4 and maintained for 1 hour. Then, the glass fiber felt was immersed for 16 hours to obtain a composite gel material. The solution temperature needed to be maintained at 75°C during the whole process.
[0051] (4) After the impregnation is completed, the composite gel material is aged at 65°C for 30 hours, fully replaced with anhydrous ethanol, and then dried with supercritical carbon dioxide to obtain silica aerogel insulation felt.
[0052] Comparative Example 2: A method for preparing a silica aerogel thermal insulation felt, the specific steps are as follows:
[0053] (1) 5.5 g of chitosan was dissolved in a mixed solution of 50 g of trifluoroacetic acid and 50 g of dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.25 g of triethoxysilyl butyraldehyde and 0.4 g of perfluorooctylethyl trisiloxane were mixed with 80 g of dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The mixture was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 30 h, the mixture was loaded into a glass syringe and electrospun under an applied electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The mixture was crushed and then dried under vacuum for 4 days. The mixture was dispersed in deionized water to obtain a 1% chitosan fiber solution.
[0054] (2) Wash 732 strong acid styrene cation exchange resin with hot water at 75°C until the effluent is colorless, then place the cation exchange resin in an exchange column and soak it with 2 times the amount of 1 mol / L H2SO4 for 2 h, then rinse it with 4 times the amount of 2 mol / L H2SO4, and finally wash it with a large amount of deionized water until it is neutral to obtain a pretreated cation resin; dissolve sodium silicate powder in deionized water to obtain 100 ml of a sodium silicate solution with a SiO2 content of 10%; dissolve agarose in deionized water at 70°C to obtain 100 ml of agarose solution with a content of 5%;
[0055] (3) Pour 200 ml of sodium silicate solution into 700 ml of pretreated cation exchange resin to remove sodium ions in the sodium silicate solution, thereby obtaining a silicic acid solution, then mix 200 ml of 10% silicic acid solution with 100 ml of 5% agarose solution, then add 25 ml of chitosan fiber solution, stir evenly, add sodium hydroxide to adjust the pH to 5.4, maintain for 1 hour, and then immerse the glass fiber felt for 16 hours to obtain a composite gel material. The solution temperature needs to be maintained at 75°C during the whole process;
[0056] (4) After the impregnation is completed, the composite gel material is aged at 65°C for 30 hours, fully replaced with anhydrous ethanol, and then dried with supercritical carbon dioxide to obtain silica aerogel insulation felt.
[0057] Comparative Example 3: A method for preparing a silica aerogel thermal insulation felt, the specific steps are as follows:
[0058] (1) 2.75 g of chitosan was dissolved in a mixed solution of 25 g of trifluoroacetic acid and 25 g of dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.125 g of triethoxysilyl butyraldehyde and 0.2 g of perfluorooctylethyl trisiloxane were mixed with 40 g of dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The mixture was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 30 h, the mixture was loaded into a glass syringe and electrospun under an applied electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The mixture was crushed and then dried under vacuum for 4 days. The mixture was dispersed in deionized water to obtain a 0.5% chitosan fiber solution.
[0059] (2) 2.75 g agarose was dissolved in a mixed solution of 25 g trifluoroacetic acid and 25 g dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.125 g triethoxysilylbutyraldehyde and 0.2 g perfluorooctylethyltrisiloxane were mixed with 40 g dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The solution was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 30 h, the solution was loaded into a glass syringe and electrospun under an applied electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The solution was crushed and then dried under vacuum for 4 days. The solution was dispersed in deionized water to obtain a 0.5% agarose fiber solution.
[0060] (3) Wash 732 strong acid styrene cation exchange resin with hot water at 75°C until the effluent is colorless, then place the cation exchange resin in an exchange column and soak it with 2 times the amount of 1 mol / L H2SO4 for 2 h, then rinse it with 4 times the amount of 2 mol / L H2SO4, and finally wash it with a large amount of deionized water until it is neutral to obtain a pretreated cation resin; dissolve sodium silicate powder in deionized water to obtain 100 ml of a sodium silicate solution with a SiO2 content of 10%; dissolve agarose in deionized water at 70°C to obtain 100 ml of agarose solution with a content of 5%;
[0061] (4) Pour 200 ml of sodium silicate solution into 700 ml of pretreated cation exchange resin to remove sodium ions in the sodium silicate solution, thereby obtaining a silicic acid solution, then mix 200 ml of 10% silicic acid solution with 100 ml of 5% agarose solution, then add 12.5 ml of chitosan fiber solution and 12.5 ml of agarose fiber solution, stir evenly, add sodium hydroxide to adjust the pH to 5.4, maintain for 1 hour, and then immerse the glass fiber felt for 16 hours to obtain a composite gel material. The solution temperature needs to be maintained at 75°C during the whole process;
[0062] (5) After the impregnation is completed, the composite gel material is aged at 65°C for 30 hours, fully replaced with anhydrous ethanol, and then dried with supercritical carbon dioxide to obtain silica aerogel insulation felt.
[0063] Comparative Example 4: A method for preparing a silica aerogel thermal insulation felt, the specific steps are as follows:
[0064] (1) 7.5 g of chitosan and 3.5 g of agarose were dissolved in a mixed solution of 50 g of trifluoroacetic acid and 50 g of dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.25 g of triethoxysilyl butyraldehyde and 0.4 g of perfluorooctylethyl trisiloxane were mixed with 80 g of dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The mixture was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 30 h, the mixture was loaded into a glass syringe and electrospun under an applied electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The mixture was crushed and then dried under vacuum for 4 days. The mixture was dispersed in deionized water to obtain a 1% composite fiber solution.
[0065] (2) Wash 732 strong acid styrene cation exchange resin with hot water at 75°C until the effluent is colorless, then place the cation exchange resin in an exchange column and soak it with 2 times the amount of 1 mol / L H2SO4 for 2 h, then rinse it with 4 times the amount of 2 mol / L H2SO4, and finally wash it with a large amount of deionized water until it is neutral to obtain a pretreated cation resin; dissolve sodium silicate powder in deionized water to obtain 100 ml of a sodium silicate solution with a SiO2 content of 10%; dissolve agarose in deionized water at 70°C to obtain 100 ml of agarose solution with a content of 5%;
[0066] (3) Pour 200 ml of sodium silicate solution into 700 ml of pretreated cation exchange resin to remove sodium ions in the sodium silicate solution, thereby obtaining a silicic acid solution. Subsequently, 200 ml of 10% silicic acid solution was mixed with 100 ml of 5% agarose solution. Subsequently, 25 ml of composite fiber solution was added. After stirring evenly, sodium hydroxide was added to adjust the pH to 5.4 and maintained for 1 hour. Then, the glass fiber felt was immersed for 16 hours to obtain a composite gel material. The solution temperature needed to be maintained at 75°C during the whole process.
[0067] (4) After the impregnation is completed, the composite gel material is aged at 65°C for 30 hours, fully replaced with anhydrous ethanol, and then dried with supercritical carbon dioxide to obtain silica aerogel insulation felt.
[0068] Comparative Example 5: A method for preparing a silica aerogel thermal insulation felt, the specific steps are as follows:
[0069] (1) 3.5 g of chitosan and 7.5 g of agarose were dissolved in a mixed solution of 50 g of trifluoroacetic acid and 50 g of dichloromethane, and stirred to obtain a mixed solution. Subsequently, 0.25 g of triethoxysilyl butyraldehyde and 0.4 g of perfluorooctylethyl trisiloxane were mixed with 80 g of dimethyl sulfoxide, stirred to obtain a mixed solution, and then added to the mixed solution. The mixture was mixed in a planetary centrifuge for 20 min. After stirring at room temperature for 30 h, the mixture was loaded into a glass syringe and electrospun under an applied electrostatic field of 15 kV / 12 cm and a flow rate of 0.5 mL / h. The mixture was crushed and then dried under vacuum for 4 days. The mixture was dispersed in deionized water to obtain a 1% composite fiber solution.
[0070] (2) Wash 732 strong acid styrene cation exchange resin with hot water at 75°C until the effluent is colorless, then place the cation exchange resin in an exchange column and soak it with 2 times the amount of 1 mol / L H2SO4 for 2 h, then rinse it with 4 times the amount of 2 mol / L H2SO4, and finally wash it with a large amount of deionized water until it is neutral to obtain a pretreated cation resin; dissolve sodium silicate powder in deionized water to obtain 100 ml of a sodium silicate solution with a SiO2 content of 10%; dissolve agarose in deionized water at 70°C to obtain 100 ml of agarose solution with a content of 5%;
[0071] (3) Pour 200 ml of sodium silicate solution into 700 ml of pretreated cation exchange resin to remove sodium ions in the sodium silicate solution, thereby obtaining a silicic acid solution. Subsequently, 200 ml of 10% silicic acid solution was mixed with 100 ml of 5% agarose solution. Subsequently, 25 ml of composite fiber solution was added. After stirring evenly, sodium hydroxide was added to adjust the pH to 5.4 and maintained for 1 hour. Then, the glass fiber felt was immersed for 16 hours to obtain a composite gel material. The solution temperature needed to be maintained at 75°C during the whole process.
[0072] (4) After the impregnation is completed, the composite gel material is aged at 65°C for 30 hours, fully replaced with anhydrous ethanol, and then dried with supercritical carbon dioxide to obtain silica aerogel insulation felt.
[0073] Performance Testing
[0074] Thermal conductivity: tested according to GB / T 10294-2008, the test results are shown in Table 1;
[0075] Water repellency: tested according to GB / T 10299-2011, the test results are shown in Table 1;
[0076] Density: tested according to GB / T 34336-2017, the test results are shown in Table 1;
[0077] Table 1 Performance test results:
[0078]
[0079] Data analysis: The silica aerogel thermal insulation felt of the present invention has low density, excellent mechanical properties, high waterproof performance and thermal insulation performance.
[0080] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the present invention further improves the compatibility and interaction between chitosan and agarose by adding the silane coupling agent triethoxysilylbutyraldehyde when preparing the composite fiber, so that the particle size of the fiber obtained by electrospinning is finer and the structure is more stable. The finer fiber can further reduce the influence of the reinforcement on the aerogel pores, and when it is used for aerogel thermal insulation felt, its flexural strength and thermal insulation performance can be further improved.
[0081] It can be seen from Example 2 and Comparative Examples 2 and 3 in Table 1 that the present invention prepares composite fibers by mixing agarose and chitosan, so that the mechanical strength and thermal insulation performance of the thermal insulation felt are improved. This is mainly because, on the one hand, the composite fibers formed by agarose and chitosan have better compatibility and dispersibility than those formed by spinning agarose and chitosan separately, and can be evenly distributed in the aerogel network. At the same time, the composite fibers themselves also have a more complex internal structure. This complex structure can effectively block the heat conduction path and can form a multi-layer barrier in the aerogel, which can further enhance the thermal insulation effect. On the other hand, in the composite fibers, the functional groups between chitosan and agarose can undergo more cross-linking reactions to form denser cross-linking points, thereby improving the mechanical strength of the aerogel, preventing it from shrinking or collapsing during the drying process, and maintaining a good microstructure.
[0082] It can be seen from Example 2 and Comparative Example 4 in Table 1 that the present invention prepares composite fibers by mixing agarose and chitosan with each other, and further adjusting the ratio between agarose and chitosan. Although the mechanical properties of the thermal insulation felt can be kept basically unchanged, its thermal insulation performance can be improved to a certain extent. This is mainly because the composite fibers formed by agarose and chitosan in a 1:1 ratio have the smallest average diameter of the composite fibers obtained by spinning compared with the composite fibers formed in other ratios, which can further reduce the adverse effect on the thermal insulation performance of the thermal insulation felt caused by the excessive particle size and the influence on the pores.
[0083] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing a silica aerogel thermal insulation felt, characterized in that: The following steps are involved: S1: mixing the silicic acid solution, the agarose solution, and the composite fiber solution to obtain a premixed solution; S2: Maintain the temperature of the premixed solution at 70-80°C, adjust the pH to 5-6, and maintain for 0.5-1h to obtain a gel solution; S3: immersing the porous material in the gel solution for 12-24 hours to obtain a composite gel material; S4: aging the composite gel material, replacing it with anhydrous ethanol, and finally drying it with supercritical carbon dioxide to obtain a silica aerogel thermal insulation felt; The preparation steps of the composite fiber solution in step S1 are as follows: dissolving chitosan and agarose in a mixed solution of trifluoroacetic acid and dichloromethane, stirring evenly to obtain a mixed solution, then mixing triethoxysilyl butyraldehyde and perfluorooctylethyl trisiloxane with dimethyl sulfoxide, stirring evenly, adding them to the mixed solution, and mixing them in a planetary centrifuge for 20 minutes, stirring at room temperature for 24-36 hours, loading them into a glass syringe, electrospinning, crushing, and then drying them under a vacuum environment for 3-5 days to obtain composite fibers, dispersing them in deionized water to obtain a 1% composite fiber solution; The weight ratio of the silicic acid solution, the agarose solution and the composite fiber solution in step S1 is 2:1:0.2-0.
3.
2. The method for preparing the silica aerogel thermal insulation felt according to claim 1, characterized in that: The SiO2 content of the silicic acid solution in step S1 is 10%, and the preparation steps are as follows: sodium silicate powder is dissolved in deionized water to obtain a sodium silicate solution with a SiO2 content of 10%, and then the sodium silicate solution is poured into a pretreated cation exchange resin to obtain a silicic acid solution with a content of 10%.
3. The method for preparing the silica aerogel thermal insulation felt according to claim 2, characterized in that: The pretreated cation exchange resin is 732 strong acid styrene cation exchange resin, which is first washed with hot water at 70-80°C until the effluent is colorless, then placed in an exchange column and soaked with 2 times the amount of 1 mol / L H2SO4 for 2 hours, then rinsed with 4 times the amount of 2 mol / L H2SO4, and finally washed with a large amount of deionized water until neutral.
4. The method for preparing the silica aerogel thermal insulation felt according to claim 1, characterized in that: The content of the agarose solution in step S1 is 5%.
5. The method for preparing the silica aerogel thermal insulation felt according to claim 1, characterized in that: The relative molecular mass of the chitosan in step S1 is 200,000.
6. The method for preparing the silica aerogel thermal insulation felt according to claim 1, characterized in that: The weight ratio of chitosan, agarose, trifluoroacetic acid, dichloromethane, triethoxysilylbutyraldehyde, perfluorooctylethyltrisiloxane and dimethyl sulfoxide in step S1 is 5-6g:5-6g:45-55g:45-55g:0.2-0.3g:0.3-0.5g:50-100g.
7. The method for preparing the silica aerogel thermal insulation felt according to claim 1, characterized in that: The pH adjustment in step S2 is performed using sodium hydroxide.
8. The method for preparing the silica aerogel thermal insulation felt according to claim 1, characterized in that: The porous material in step S3 is selected from one of knitted glass fiber felt, melamine sponge, activated carbon fiber felt, glass fiber polyester mixed felt, viscous fiber felt and ceramic fiber felt.
9. The method for preparing the silica aerogel thermal insulation felt according to claim 1, characterized in that: The aging temperature in step S4 is 50-80° C., and the aging time is 16-48 hours.
10. A silica aerogel thermal insulation felt, characterized in that: The silica aerogel thermal insulation felt is prepared according to the preparation method of the silica aerogel thermal insulation felt according to any one of claims 1-9.
Citation Information
Patent Citations
A method for preparing aerogel felt thermal insulation material
CN108996985B
High-temperature resistant silica aerogel heat preservation felt preparation method
CN109574622A
Inorganic material
CN101838134A
SiO2 aerogel / inorganic cotton compound thermal insulation felt and preparation method thereof
CN102701700A